THE IMPACT OF SALES PROMOTION AND PERCEIVED VALUE ON REPURCHASE INTENTION: A CASE STUDY ON SAMUDRA SUPERMARKET CONSUMERS IN MALANG CITY - Arifa, Ziada Elma; Vania, Amelindha (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to examine the impact of sales promotion and perceived value on repurchase intention among consumers of Samudra Supermarket in Malang. A quantitative approach was applied using data from 110 respondents, selected through purposive sampling. The data was analyzed using Smart PLS software to test the hypotheses. The findings reveal that sales promotion does not significantly influence repurchase intention, while perceived value has a positive and significant effect on repurchase intention. These results highlight the importance of perceived value in fostering customer loyalty, suggesting that Samudra Supermarket should focus on improving customer perceptions of value to encourage repeat purchases.